2019
DOI: 10.1186/s41476-019-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Tapered photonic crystal fibers coated with ultra-thin films for highly sensitive bio-chemical sensing

Abstract: Background: Photonic crystal fiber Mach-Zehnder modal interferometers based on no adiabatic tapered fibers are perspective for bio-chemical sensing, since they have very high refractive index sensitivity and it is possible for them to use a very small quantity of investigated samples. To obtain a desirable sensitivity to a needed analyte, it was proposed to coat a sensing surface of the refractive index sensor with ultra-thin films. Methods: In this work, we reported on a no adiabatic tapered special photonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Thus, the sensing of different gases or any other chemicals is observable. To confirm of the principle, we demonstrated the sensing of hydrogen [42,43]. Hydrogen is one of the cleanest energy sources.…”
Section: Gas Detectionmentioning
confidence: 84%
“…Thus, the sensing of different gases or any other chemicals is observable. To confirm of the principle, we demonstrated the sensing of hydrogen [42,43]. Hydrogen is one of the cleanest energy sources.…”
Section: Gas Detectionmentioning
confidence: 84%
“…In addition to the measurement of pH by filling liquid crystal in PCF, the PCF sensor also realizes the rapid detection of most antigens and antibodies. The same year, Vladimir P Minkovich et al reported a non‐adiabatic tapered PCF probe that can detect biomolecules, as shown in Figure 7 [69]. The experimental results show that the detection limit of Bovine albumin (BSA) antibody concentration is 125 pg/mL.…”
Section: The Principle and Applications Of Biosensors Based On Specialty Fiber Interferometermentioning
confidence: 99%
“…A, The scanning electron microscope of photonic crystal fiber (PCF) cross section (left) and diagram of tapered PCF (right); B, Sensor response with anti‐BSA concentration between 0.125 and 125 ng/mL [69]…”
Section: The Principle and Applications Of Biosensors Based On Specialty Fiber Interferometermentioning
confidence: 99%
“…Optical fiber sensor is a device, which is used for measuring various physical parameters by the changes of physical characteristics such as interference, diffraction, polarization, reflection and loss of light caused by light propagation in the optical fiber [1][2][3][4][5][6][7][8]. The optical fiber offer many excellent characteristics such as low loss, wide frequency band, large amount of information, small size, light weight, and good winding property.…”
Section: Introductionmentioning
confidence: 99%